Intraoperative Imaging in Hepatopancreatobiliary Surgery - Husarova, Tereza; MacCuaig, William M; Dennahy, Isabel S; Sanderson, Emma J; Edil, Barish H; Jain, Ajay; Bonds, Morgan M; McNally, Molly W; Menclova, Katerina; Pudil, Jiri; Zaruba, Pavel; Pohnan, Radek; et al. (Cancers, 2023)
Hepatopancreatobiliary surgery belongs to one of the most complex fields of general surgery. An intricate and vital anatomy is accompanied by difficult distinctions of tumors from fibrosis and inflammation; the identification of precise tumor margins; or small, even disappearing, lesions on currently available imaging. The routine implementation of ultrasound use shifted the possibilities in the operating room, yet more precision is necessary to achieve negative resection margins. Modalities utilizing fluorescent-compatible dyes have proven their role in hepatopancreatobiliary surgery, although this is not yet a routine practice, as there are many limitations. Modalities, such as photoacoustic imaging or 3D holograms, are emerging but are mostly limited to preclinical settings. There is a need to identify and develop an ideal contrast agent capable of differentiating between malignant and benign tissue and to report on the prognostic benefits of implemented intraoperative imaging in order to navigate clinical translation. This review focuses on existing and developing imaging modalities for intraoperative use, tailored to the needs of hepatopancreatobiliary cancers. We will also cover the application of these imaging techniques to theranostics to achieve combined diagnostic and therapeutic potential.